The Franchisee Handbook - Siebert, Mark (Ascent Audio, 2019)
Mark Siebert, franchise expert and author of Franchise Your Business, flips his script from franchising your existing business to offer entrepreneurs a comprehensive guide to succeeding as franchisees. The Franchisee Handbook shows listeners how to take a systematic approach to assess and invest in franchise opportunities so they end up with the right fit for their entrepreneurial style. Sharing tales from the trenches and real-world anecdotes from successful franchises (and a few cautionary tales from those who didn't make it), Siebert lays out everything you need to know before signing with well-known franchises from locally-owned names to global brands. As an expert witness, he has seen a number of failed franchisees (especially in the last ten years) and will dish the dirt on what successful franchisees have in common and how they play to win. And those cautionary tales? Many went into franchising with the expectation that franchising was a silver bullet that did not require hard work or skills. Siebert will dispel that myth and show prospective franchisees a proven, logical, step-by-step method to close the sale and set themselves up for long-term franchise success.